Initial Stage of Nucleate Boiling: Molecular Dynamics Investigation - Takahiro YAMAMOTO; Mitsuhiro MATSUMOTO (Journal of Thermal Science and Technology, 2012)
We investigated the initial stage of nucleate boiling on ideally smooth surface with a molecular dynamics simulation technique. Lennard-Jones (LJ) model liquid was confined in a rectangular simulation cell, contacting with a flat smooth solid wall. The wall consists of fcc crystal of LJ-like particles. After the system was thermally equilibrated, the temperature of wall particles was raised to transfer thermal energy to the liquid. We examined two cases, the overall heating where the surface temperature is kept constant all over the area, and the partial (spot) heating where two regions of heating and cooling are placed. In both cases, when the liquid in the vicinity of the heating surface obtains sufficient energy, it thermally expands and its pressure decreases, leading to formation of bubble nuclei of atomic size. The inception time of nucleation was found to be affected by surface wettability as well as the surface temperature. When the surface is hydrophobic and the heating area is small, size oscillation of the generated bubbles was observed.